Surgical management of foramen magnum meningiomas: Clinical insights and outcomes (Annals of Medical Research, 2024)
Aim: This retrospective study aimed to provide a comprehensive analysis of the surgical management of foramen magnum meningiomas (FMMs), focusing on patient characteristics, surgical approaches, complications, and postoperative outcomes.Materials and Methods: The study included 23 patients diagnosed with anterior or anterolateral FMMs who underwent surgical treatment between 2014 and 2022. The study encompassed clinical records, neurological assessments, radiological findings, and surgical approaches, with a focus on the far lateral approach (FLA). Evaluation of outcomes included Karnofsky Performance Scale (KPS) scores and The Neck Disability Index (NDI) scores. Surgical approaches and postoperative care strategies were detailed. The study also examined the relationship between tumor location and surgical techniques.Results: The analysis revealed that patients with FMMs presented with various clinical symptoms, including lower cranial nerve deficits, pyramidal tract syndrome, and sensory disturbances. The retrocondylar far lateral approach was predominantly utilized, resulting in various Simpson resection grades. Postoperative complications were observed, including cranial nerve deficits, cerebrospinal fluid leakage, and infections. Also, the study found patient KPS scores remained stable, and NDI scores showed no significant increases before and after surgery.Conclusion: Surgical management of FMMs is a complex task requiring meticulous planning, individualized approaches, and close attention to neurovascular structures. The study emphasized the diverse clinical presentations and surgical techniques associated with FMMs and highlighted the importance of ongoing research and collaborative efforts to enhance patient care in this challenging field.
Keywords: Foramen magnum meningiomas; Surgical management; Far lateral approach; Complications; Patient outcomes